2013
DOI: 10.1111/1753-0407.12104
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between platelet volume indices with macrovascular and peripheral neuropathy complications in type 2 diabetic patients (2型糖尿病患者血小板容积参数与大血管及外周神经并发症的相关性研究)

Abstract: These findings implied the predictive value of platelets volume indices in vascular and peripheral neuropathy complications in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…Secondary risk factors are smoking and prediabetes [1,21,60,63]. Platelet activation [79][80][81][82], oxidative stress [65][66][67][68][69][70][71][72][73][74], low vitamin D [83,84], insulin resistance [58], and genetic factors [100][101][102][103][104][105][106] play another supplementary role, but, for the time being, there are limited options for intervention. A suggestion for targeting insulin resistance originates from the study by Pop-Busui et al, showing that reduced incident DSPN is less frequent in T2D patients receiving insulin-sensitizing oral agents (66%) than in those receiving insulinproviding treatment (66% vs. 72%, respectively, p = 0.02) [155].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary risk factors are smoking and prediabetes [1,21,60,63]. Platelet activation [79][80][81][82], oxidative stress [65][66][67][68][69][70][71][72][73][74], low vitamin D [83,84], insulin resistance [58], and genetic factors [100][101][102][103][104][105][106] play another supplementary role, but, for the time being, there are limited options for intervention. A suggestion for targeting insulin resistance originates from the study by Pop-Busui et al, showing that reduced incident DSPN is less frequent in T2D patients receiving insulin-sensitizing oral agents (66%) than in those receiving insulinproviding treatment (66% vs. 72%, respectively, p = 0.02) [155].…”
Section: Discussionmentioning
confidence: 99%
“…Mean platelet volume (MPV) is a marker of platelet activation, and may be increased in diabetes patients, especially in the context of microvascular complications [80]. Elevated MPV has indeed been reported in T2D patients with DSPN [81,82].…”
Section: Platelet Activationmentioning
confidence: 99%
“…Increased MPV has been demonstrated in diabetes (3)(4)(5)(6)(7)(8)(9). There are conflicting results about the relation of MPV with diabetic nephropathy/microalbuminuria (MA) (10)(11)(12)(13)(14)(15)(16)(17), diabetic neuropathy (18)(19)(20), coronary artery disease (4,13,18,(21)(22)(23)(24)(25), and cerebrovascular disease (3)(4)(5)26) in diabetic patients. Large platelets may play a role in the development of vascular damage in DR by being more active, forcing 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that MPV, PCT, PDW, and P-LCR levels are higher in diabetics than in non-diabetic individuals (22)(23)(24) . Several authors have also suggested that increased MPV and PDW are associated with the presence of diabetes-related complications in T2DM patients (24)(25)(26) . On the other hand, it has been observed that platelet indices tend to decrease in patients with good glycemic control (5,27,28) .…”
Section: Discussionmentioning
confidence: 99%